2018
DOI: 10.1039/c8nr05494k
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast fabrication of nickel sulfide film on Ni foam for efficient overall water splitting

Abstract: Development of low-cost, high performance and stable non-noble electrocatalysts with both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) activities for overall water splitting is essential for future energy supply. Herein, for the first time, a facile and ultrafast synthetic method has been reported to fabricate nickel sulfide (Ni3S2) films on Ni foam (Ni3S2/NF) as efficient bifunctional electrodes for overall water splitting through direct dropping of mercaptoethanol solution followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 52 publications
3
48
0
Order By: Relevance
“…[1i,33] Interestingly, there is no evidence of oxidation into phosphate surface species upon exposure to atmosphere as there is no peak present at 134 eV. [33a] After the OER, there are some significant chemical changes whereby the peak at 852.5 eV disappears due to the conversion of metallic Ni to oxides or hydroxides (Figure 6b4), [12] with also evidence of NiOOH formation as indicated by a peak at 855.7 eV. [23] The P 2p doublet peak at 130 eV decreased dramatically in intensity (Figure 6b5) with the emergence of a peak at around 133 eV which is attributed to phosphate formation, [34] or oxidized species of P. [1p,15] This appears to be in slight contradiction to another study by Stern et al [35] who demonstrated the formation of a core-shell Ni 2 P/NiO x structure as the active form for the OER which is generated in-situ from Ni 2 P during the OER, but with no evidence of phosphate species retained on the surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1i,33] Interestingly, there is no evidence of oxidation into phosphate surface species upon exposure to atmosphere as there is no peak present at 134 eV. [33a] After the OER, there are some significant chemical changes whereby the peak at 852.5 eV disappears due to the conversion of metallic Ni to oxides or hydroxides (Figure 6b4), [12] with also evidence of NiOOH formation as indicated by a peak at 855.7 eV. [23] The P 2p doublet peak at 130 eV decreased dramatically in intensity (Figure 6b5) with the emergence of a peak at around 133 eV which is attributed to phosphate formation, [34] or oxidized species of P. [1p,15] This appears to be in slight contradiction to another study by Stern et al [35] who demonstrated the formation of a core-shell Ni 2 P/NiO x structure as the active form for the OER which is generated in-situ from Ni 2 P during the OER, but with no evidence of phosphate species retained on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently Ren et al . reported the bifunctionality of Ni foam after converting the surface into Ni 3 S 2 . However after post OER analysis, they postulated that the amorphous Ni(OH) x formed on the surface was the active species for the OER.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the preparation methods require high‐temperature annealing treatments and long hydrothermal reactions, which are complicated, time‐consuming, and energy‐intensive. Moreover, some of the preparation processes, such as sulfuration and phosphorization, often involve toxic sulfur‐ or phosphorus‐containing gases . In addition, traditional electrode preparation techniques require the powder catalysts to be adhered to conducting substrates by using a polymer binder, such as Nafion, which often affects the stability of the catalysts and leads to “dead volume” .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, efficient, stable, and large‐scaled OER electrocatalysts are highly essential for the overall water splitting. To replace the benchmark OER catalyst of IrO 2 or RuO 2 , the first‐row transition metals such as Ni‐based sulfides, hydroxides, oxy‐hydroxides, and nitrides have been extensively studied due to the low cost, earth abundance, and low‐temperature synthesis. However, the low overpotential and high stability still remain a great challenge toward OER.…”
Section: Introductionmentioning
confidence: 99%